Awareness and use of telephone‐based behaviour change support services among clients of a community mental health service. (26th October 2020) - Fehily, Caitlin; Latter, Joanna; Bartlem, Kate; Wiggers, John; Bradley, Tegan; Rissel, Chris; Reakes, Kate; Reid, Kate; Browning, Ellen; Bowman, Jenny
Abstract: Objective : To determine the prevalence of, and factors associated with, awareness and use of telephone‐based behaviour change support services among clients of a community mental health service. Methods : Adult clients (n=375) of one Australian community mental health service completed a telephone interview and self‐reported not meeting Australian National Guidelines for smoking, nutrition, alcohol consumption and/or physical activity. Descriptive statistics summarised awareness and use of the New South Wales Quitline ® and Get Healthy Service ® for participants with lifestyle risk factors addressed by each service. Chi‐squares and logistic regressions explored associations between client characteristics, and service awareness and use. Results : Awareness (16.1%) and use (1.9%) of the Get Healthy Service was lower than that of Quitline (89.1%; 18.1%). Television was the most common source of awareness (39.7% Get Healthy Service; 74.0% Quitline). In the regression models, persons in a relationship were more likely to have heard of the Get Healthy Service (OR:2.19, CI:1.15–4.18), and persons aged 36–50 were more likely to have used the Quitline (OR:5.22, CI:1.17–23.37). Conclusions : Opportunities exist for increasing awareness and use of both services, particularly the Get Healthy Service, among clients of community mental health services. Implications for public health : Strategies to optimise reach for this population group are recommended.